Pengaruh Budaya Kerja dan Pengawasan Terhadap Kinerja Karyawan (Studi Kasus di PT Bank DKI Capem Syariah Margonda, Depok) - Iqbal, Muhammad (Institut Ilmu Sosial dan Manajemen STIAMI, 2017)
Work Culture Influence and Supervision of Employee Performance in PT Bank DKI Sharia Capem Margonda, Depok. This study stems from the emergence of the phenomenon that the performance of the employees of Bank DKI Sharia Capem Margonda, Depok not run optimally, because they found that the employee's performance is not optimal, it is seen from the phenomenon has not grown maximum employee morale, not maximal work discipline in accordance with what is expected, still slow service work done on the client, still less cepeta in response to complaints or complaints from customers, is still not maximal work as expected, and so forth. The poor performance caused by many factors including work culture, supervision, planning, work motivation, work ethic, budgeting, productivity and so on, but researchers suspect that the most critical factors that affect the performance of the employee is deemed work culture and supervision. The purpose of this study was to menganilisis how much influence the work culture and supervision of employee performance.The sampling method used is saturated sample, where all the population of 40 employees sampled, because there is not much .. The data that have met the test of validity and reliability testing further processed to produce a regression equation Y = 0.242+ 0286 X1 + 0699 X2, where Y is the variable performance of the employee, is the variable X1 and X2 are working culture control variables.Hypothesis testing using t test showed that each of the independent variables studied was shown to significantly partial effect on the dependent variable employee performance. Then through the F test can be seen that both the independent variables studied proved simultaneously affect the dependent variable employee performance. Figures Adjusted R Square of 0.5625 indicates that the work culture together with monitoring employee performance variables can be explained by 56.25%, while the remaining 43.75% is explained by other variables.